[PP.06.09] POTENTIAL IMPACT OF STATIN USE ON DAY-TIME AND NIGHT-TIME BLOOD PRESSURE LEVELS: A RETROSPECTIVE ANALYSIS OF A LARGE DATABASE OF 24-HOUR AMBULATORY BLOOD PRESSURE MONITORING. (September 2017) - Tocci, G.; Presta, V.; Figliuzzi, I.; Costanzi, V.; Gallo, G.; Attalla, N.; Simonelli, F.; Citoni, B.; Battistoni, A.; Ferrucci, A.; Volpe, M.
Abstract : Objective: Introduction. Assumption of drugs inhibiting the hydroxy-methyl-glutaril-coA (or statins) is recommended at bed-time and evidence demonstrated a strong and independent correlation between night-time blood pressure (BP) and increased risk of cardiovascular events. Design and method: Aim. To evaluate the effects of statins on night-time BP levels. Methods. We analysed data derived from a large cohort of adult individuals, who consecutively underwent home, clinic and ambulatory BP monitoring at our Unit. All BP measurements were performed and BP thresholds were set according to recommendations from European guidelines. Study population was stratified according to statin use. Results: Results. We included an overall sample of 5, 634 adult individuals (female 48.9%, age 60.511.6 years, BMI 27.04.6 kg/m 2, clinic BP 144.318.4/90.912.4 mmHg, 24-hour BP 130.713.4/79.09.7 mmHg), among whom 17.3% received and 82.7% did not received statins. Treated outpatients were older, had higher BMI and prevalence of risk factors and comorbidities than those who were untreated (P < 0.001 for all). Although they received more antihypertensive agents, they showed lower diastolic BP levels at all BP measurements, including night-time (67.39.4 vs. 70.99.7 mmHg; P < 0.001) periods, than those observed in untreated patients. Statin use was also associated with lower diastolic BP load during night-time period (43.428.9 vs. 52.329.5; P < 0.001). Finally, statin use resulted the strongest and independent factor associated with 24-hour [OR (95% CI): 1–513 (1.295–1.767); P < 0.001] and night-time [OR (95% CI): 1.357 (1.161–1.587); P < 0.001] BP control, even after adjusting for age, BMI, number of antihypertensive drugs and diabetes. Conclusions: Conclusions. Statin use was associated to a significantly lower diastolic BP levels. These effects were independently observed, even after correction for major cardiovascular risk factors and comorbidities, as well as number and type of antihypertensive drug classes.